A carbon-functionality-appended diborylacetylene available for a component of organic synthesis and OLEDs. Issue 32 (4th April 2022) - Tsukada, Tetsuyoshi; Shoji, Yoshiaki; Takenouchi, Kumiko; Taka, Hideo; Fukushima, Takanori
Abstract : Newly synthesized 1, 2-diborylacetylene with planar 9-oxa-10-boraanthracene termini has excellent stability toward air and moisture and even allows thermal treatment for the preparation of thin films for OLEDs, and further it shows chemical reactivity typical of alkynes. Abstract : We present new 1, 2-diborylacetylene derivatives with planar 9-oxa-10-boraanthracene termini, which display excellent stability to allow usual handling and even thermal evaporation for the preparation of thin films for OLEDs, and also undergo typical reactions of alkynes such as the Diels–Alder reaction.